Five Decades of Theology in Spain - Bueno de la Fuente, Eloy (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
In his inaugural address at the Council, Pope John XXIII spokes about the aggiornamento of the Church, and the spirit of a pastoral teaching became the identity sign of his Council. Vatican II is seen by the experts as an event capable to renew the Church and the theology. The present article analyzes the development of the Theology in Spain in the last five decades. In an effort at synthesis and crispness, the author offers an overview of the theological evolution before and after Vatican II. New times, new necessities of mission that requires the renovation of theology.
Keywords: Second Vatican Council; Review of Theology; reception of the council; theologians.